2022
DOI: 10.1021/acs.inorgchem.2c02332
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Complexation Mechanism of a Promising Lipophilic PyTri Ligand for Actinide Partitioning from Spent Nuclear Fuel

Abstract: The challenging issue of spent nuclear fuel (SNF) management is being tackled by developing advanced technologies that point to reduce environmental footprint, long-term radiotoxicity, volumes and residual heat of the final waste, and to increase the proliferation resistance. The advanced recycling strategy provides several promising processes for a safer reprocessing of SNF. Advanced hydrometallurgical processes can extract minor actinides directly from Plutonium and Uranium Reduction Extraction raffinate by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The third phase was dissolved by adding 1 M nitric acid pre-equilibrated organic phase and the LOC and LAS were determined in the organic phase immediately after the dissolution of the third phase. 37,38 bNT – no third phase formation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The third phase was dissolved by adding 1 M nitric acid pre-equilibrated organic phase and the LOC and LAS were determined in the organic phase immediately after the dissolution of the third phase. 37,38 bNT – no third phase formation.…”
Section: Resultsmentioning
confidence: 99%
“…The LOC and CAC of nitric acid were determined by acid-base titration. 29,37,38 2.5 Dynamic light scattering 2.5.1 Theory of dynamic light scattering. The underlying principle of the dynamic light scattering technique is based on Brownian motion, where the reverse micellar aggregates present in the organic phase undergo a constant random motion due to collision with the solvent molecules present in the sample.…”
Section: Third Phase Formation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 By contrast, ESI-MS reveals the complexes or protonated ligand directly, and it has been validated as an appropriate technique for characterizing the complexes in solution. 20 The advantage of this technique is that it can quickly, directly, and accurately determine the complex species in solution and investigate their stability in the gas phase. 21 Several recent studies have shown that the complexes between the liquid-phase and gas-phase have good consistency.…”
Section: +mentioning
confidence: 99%
“…The hydrolytic and radiolytic degradation products of CyMe 4 ‐BTBP have also been reported 19 . By contrast, ESI‐MS reveals the complexes or protonated ligand directly, and it has been validated as an appropriate technique for characterizing the complexes in solution 20 . The advantage of this technique is that it can quickly, directly, and accurately determine the complex species in solution and investigate their stability in the gas phase 21 .…”
Section: Introductionmentioning
confidence: 99%